A Comparative Study of the Motivations to Teach Chinese Between Native and Non-native Pre-service CSL/CFL Teachers - Gu, Ling; Wang, Binglong; Zhang, Haiwei (Frontiers in Psychology, 2021)
The present study compared motivations to enter the teaching profession between native and nonnative pre-service Chinese as a second/foreign language (CSL/CFL) teachers. The participants included 325 native and 325 nonnative Chinese-speaking pre-service CSL/CFL teachers registered in Masters in Teaching Chinese to Speakers of Other Languages (MTCSOL) programmes; the teachers were asked to complete a 24-item questionnaire. Two major findings emerged. First, a similar six-factor teacher motivation were observed for the native and nonnative teachers. Second, the two groups showed nonsignificant differences in their ratings of the importance of cross-cultural value, intrinsic value, altruistic value and fallback career choice as types of motivation but differed significantly in their ratings of extrinsic value and social influence. These results highlight the differences and similarities in second language teacher motivation and offer insights into the variables at different levels that might influence second language teacher motivation. Teacher motivation is advised to be taken into account in the training and administration of CSL/CFL teachers to alleviate the problem of teacher shortage outside China.